An Alternative to Radial Head Excision or Arthroplasty: On Surgical Table Reconstruction of Radial Head Fractures (Annals of Medical Research, 2021)
Aim: We aimed to show that successful results can be obtained by combining the fractured parts over the operating table and fixing them with an anatomic plate in Mason type 3 - 4 multi-fragmented and / or displaced radial head fractures.
Keywords: Radius Fractures; Fractures-Comminuted; Fracture Fixation-Internal; Arthroplasty-Replacement.